The Armory Show : Tenth Edition. - Heilmann, Mary; Waters, John (New York : The Armory Show New York, 2008)
Heilmann, Mary ; Grinnan, Katie ; Jacobson, Martin ; Gersht, Ori ; VanDenBeek, Sara ; Rosefeldt, Julian ; Coste, Annelise ; Bhabha, Huma ; Wang Du ; Butzer, André ; Fitzpatrick, Daphne ; Kalenderian, Raffi ; Nishi, Tatzu ; Heikes, Jay ; Saraceno, Tomas ; Brazda, Bozidar ; Rubsamen, Glen ; Argianas, Athanasios ; Pousttchi, Bettina ; Wood, Jonas ; Bradley, Joe ; Eggleston, William ; Ross-Ho, Amanda ; Lassry, Elad ; Scanlan, Joe ; Thom, Rob ; Hug, Scott ; Tal R ; Solakov, Nedko ; Bird, Colby ; Stauss, Peter ; Hammond, Charlie ; Churm, Rob ; Caesar, Jedediah ; Anderson, Hurvin ; Parrino, Steven ; Piper, Adrian ; Tajima, Mika ; Auerbach, Tauba ; Longly, George Henry ; Skaer, Lucy ; Mayer, Maix ; Dupuis, David ; Schabus, Hans ; Antin, Eleanor ; Ruckhäberle, Christoph ; Holloway, Evan ; Armanious, Hany ; Peri, Peter ; Smith, Bridget ; Lamers, Kiki ; Craig-Martin, Jessica ; Guyton & Walker ; Sibony, Gedi ; Ruggaber, Karin ; Rogan, Will ; Guzman, Daniel ; Creed, Martin ; Friedl, Peter ; Hoener, Martin ; Bircken, Alexandra ; Hashimoto, Jacob ; Bauer, Michael ; Fridfinnsson, Hreinn ; Tixador, Laurent ; Poincheval, Abraham ; Tichy, Miroslav ; Morrison, Paul ; Wall, Jeff ; van der Werve, Guido ; Rockenschaub, Gerwald ; Hammoud, Carl ; Lemieux, Annette ; Los Carpinteros ; Collins, Phil ; Shrigley, David ; Bove, Carol ; Claydon, Steven ; Johnson, Rashid ; Matelli, Tony ; Trouvé, Tatiana ; Jones, William E. ; Ethridge, Roe ; Walde, Martin ; Rhee, Ki-Bong
The Armory Show : Tenth Edition, Pier 94, New York, 2008-03-27. 2008-03-30
boek